Forest Ecosystems in the Transition to a Green Economy and the Role of REDD+ in the United Republic of Tanzania - United Nations Environment Programme (United Nations, 2016)
The aim of this report is to assess how deforestation affects the economy of the United Republic of Tanzania, both by looking at the limited ecosystem goods and services currently reflected in GDP and by looking at the effects on the economy if the full suite of forest ecosystem services are taken into account. The findings show that investment in the forestry sector has a disproportionately positive impact on the incomes of rural households in comparison to stimulating output from other sectors, meaning that investment in forestry could contribute to alleviating poverty. Taking these findings together, this report presents a solid case for Tanzania to integrate REDD+ policies into key economic sectors such as energy, agriculture, livestock, industries, transport and water to address the drivers of deforestation and forest degradation while identifying how the implementation of REDD+ can be part of Tanzania’s broader economic and development strategy, as the country plans to move towards REDD+ results-based actions that could lead to results-based payments and then towards Green Economy pathways to sustainable development and poverty eradication in Tanzania.